Organic farming for a sustainable future: soil and yield improvement through integrated nitrogen management - Kumar, Sanjeev; Onte, Santosh; Boregowda, Yogananda Shivalli; Angadi, Airadevi P.; Pyati, Prasanna S.; Naveena, K.; Garg, Kamal; Meena, Vijendra Kumar; Chandra, Ramesh; Meena, Babu Lal; Reddy, Marthala Bhuvaneswar; Kochewad, Sanjivkumar Angadarao; et al. (Frontiers in Sustainable Food Systems, 2025)
Efficient nitrogen management is crucial for sustaining soil health, optimizing yields, and ensuring the long-term viability of organic farming systems. A cereal-legume cropping system is widely recognized for improving nutrient cycling and ecosystem services. This study investigates the impact of these treatments on soil quality, energy fractions, and yield of fodder maize-berseem-cowpea under organic farming with a focus on enhancing ecosystem services and supporting agroecological principles. A three-year field experiment (2018–19 to 2020–21) was conducted with maize (M) - berseem (B) - cowpea (C) cropping system laid in a randomized complete block design (RCBD) with three replications and seven treatments. Drawing upon the theoretical framework of sustainable agriculture and integrated nutrient management, treatment T7, (Farmyard manure (FYM) + Plant growth promoting rhizobacteria (PGPR) + 3% foliar spray of panchagavya (M) - PGPR + 3% foliar spray of panchagavya (B) - PGPR + 3% foliar spray of panchagavya (C), resulted in significant improvements in soil organic carbon (4.0–15.2%), soil organic matter content (3.8–14.7%), available nutrients (10.7–36.6%), microbial population (54.8–119.3%), and soil enzymatic activities (103.0–187.2%). Additionally, energy fractions and TDCP content showed positive trends. Yield penalties in maize declined from 11.9 to 8.09% over 3 years; berseem showed a 2.5% initial reduction but improved in subsequent years, while cowpea consistently exhibited slight yield gains. Compared to treatment T1 (100% chemical fertilizers), treatment T7 enhanced soil health and nutrient cycling with only a slight reduction in system productivity (4.3 to 7.0%), demonstrating the long-term benefits of organic inputs. This study highlights the importance of integrated nitrogen management in organic systems, reducing reliance on synthetic fertilizers while enhancing ecological sustainability. It offers a practical approach to improving soil resilience, boosting energy efficiency, and supporting sustainable development goals—providing valuable insights for policymakers and practitioners pursuing environmentally responsible agricultural practices.